Direct digital control of a D.C. machine - Weehuizen, Hermanis Frans (Department of Electrical Engineering, 2016)
The object of this thesis is to build an interface between a computor and a three phase thyristor bridge rectifier, enabling the computor to control its D.C. output voltage. By writing a suitable computor program, this system was extended to provide closed loop computor control of the speed of a D.C. machine. The first interface and computor program were so designed that the computer provided the required analogue triggering delay for voltage control of the D.C. output. This setup did not allow for infinite variation of the voltage and occupied a large portion of the computor time. Thus it was decided to modify the interface, letting it provide its own delay, thus freeing the computor of the delay routine and giving it more time to do other tasks. Control of the bridge rectifier was also improved. When closed loop control was implemented, the system was found to be unstable. It was thus simulated and stabilized on the analogue computor. A new digital computor program was written incorporating those characteristics which were found necessary in the simulation to make the system stable. The modified form of compensation was found to give a satisfactory performance for both step and ramp inputs to the system as well as load transients on the D.C. motor. Various types of tachogenerator were tested to find which was the most suitable for operation with the computer. All the types tested gave satisfactory performances. The major factor affecting performance was the quality of the tachogenerator.